1995
DOI: 10.1099/00222615-42-6-415
|View full text |Cite
|
Sign up to set email alerts
|

Electronmicroscopic investigation of the effects of biocides on Pseudomonas aeruginosa PAO bacteriophage F116

Abstract: Summary.Electronmicroscopy was used to observe morphological changes of the Pseudomonas aeruginosa PA0 bacteriophage F116 when treated with various biocides commonly used as antibacterial and antifungal agents. Because of its large size (145 nm) and its organised structure (an isometric head and a tail), it was possible to classify structural damage into eight categories. The morphological changes induced depended on the type of biocide used and its concentration. Glutaraldehyde increased the number of phages … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 18 publications
1
23
0
Order By: Relevance
“…In literature, it was observed that treatments with 70% and 100% ethanol for 30 min produced alterations in the viral capsid of the Pseudomonas aeruginosa bacteriophage, without effects on the viral DNA (Maillard, Beggs, Day, Hudson, & Russel, 1996a). Isopropanol, at a concentration of 100%, showed a similar effect on the same phage (Maillard et al, 1995;Maillard, Beggs, Day, Hudson, & Russel, 1996a, b). These findings also indicate the effectiveness of ethanol and isopropanol for bacteriophage inactivation.…”
Section: Phage Inactivation By Heat Ethanol and Isopropanolmentioning
confidence: 89%
“…In literature, it was observed that treatments with 70% and 100% ethanol for 30 min produced alterations in the viral capsid of the Pseudomonas aeruginosa bacteriophage, without effects on the viral DNA (Maillard, Beggs, Day, Hudson, & Russel, 1996a). Isopropanol, at a concentration of 100%, showed a similar effect on the same phage (Maillard et al, 1995;Maillard, Beggs, Day, Hudson, & Russel, 1996a, b). These findings also indicate the effectiveness of ethanol and isopropanol for bacteriophage inactivation.…”
Section: Phage Inactivation By Heat Ethanol and Isopropanolmentioning
confidence: 89%
“…Its large size (145 nm) and its double-stranded DNA make it a suitable model for investigating viral disinfection mechanisms, as has been shown in previous studies (Maillard et al 1995. Furthermore, the use of bacteriophage is suited for such investigations because of the properties of these bacterial viruses; a well-defined structure, non-pathogenicity, low costs of propagation, availability of large amounts of phage particles (e.g.…”
Section: Introductionmentioning
confidence: 97%
“…Representative TEM images (panel C) of soluble, purified proteins that were expressed from the sequence of 5610 resemble procapsid structures with various morphologies. The red image outlined in panel D shows an empty procapsid, which resembles a “broken” head structure (blue outlined image) of Pseudomonas aeruginosa PA0 phage F116, and is illustrated by a white inset image [51]. Panel E shows images of a “folded” head structure from the soluble, purified proteins of 5610 (red outline) that is similar to that of φF116 (blue outline with white inset image [51]).…”
Section: Resultsmentioning
confidence: 99%
“…Despite being assembled from the protein product of a single gene, the VCID5610 structures appear to have different morphotypes that are reminiscent of the damaged procapsids that result from the treatment of the Pseudomonas phage F116 with biocides, as shown by Maillard et al [51].…”
Section: Resultsmentioning
confidence: 99%